Customized Device for Pediatric Upper Limb Rehabilitation in Obstetric Brachial Palsy - López Celani, Natalia Martina (2014)
A 12-yr-old child, with a history of gestational Erb-Duchenne palsy and, later, musculoskeletal injuries in the left arm caused by a car accident, inspired the design of a customized exoskeleton-like device. Such piece, intended for rehabilitation, has one degree of freedom because the exercise routine involves elbow flexion-extension, which was indicated for the damaged muscular group. The device has two functioning modes, passive and assisted, in which the patient can trigger the movement by a biceps contraction, thus promoting the active role of the user in the rehabilitation process. The results were evaluated in terms of qualitative measures of the biceps and the triceps performed by the medical staff and by a questionnaire related to functional activities of the upper limb. A significant improvement in the arm movement and elbow angle was observed after 3 mos of assisted therapy, complementary to conventional exercises. In conclusion, a simple and low-cost device was designed and tested to complement the rehabilitation process of a pediatric patient with physical impairment.